MAKNA SELF DISCLOSURE PEREMPUAN DALAM KELUARGA (STUDI KASUS PADA PEREMPUAN KARIER DI UNIVERSITAS BUDI LUHUR) - Mulyati . (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2018)
Women's self-disclosure in the family is very important, especially as a working woman or a career woman. Self-disclosure within the family is one factor to foster interpersonal communication skills. If the self-disclosure in the family is not done well then there will be misunderstandings. The purpose of this study is to gain knowledge about the meaning of self-disclosure of women in family careers at Budi Luhur University. This study uses interpersonal communication and media theory, the theory of symbolic interactionism, self-disclosure, family communication, and the dual role of a career woman. The method used is qualitative with case study approach, because this research emphasizes on the cases of communication that is happening in the life of society, especially about self-disclosure is a form of message and communication competence with the aim to minimize misunderstandings between communicators and communicants. From the results of this study found that: Interpersonal communication is a career woman to reveal more about his identity. While the self-disclosure of a career woman with her husband about the depth of information and situations or emotional feelings while in the office. The meaning of the family according to a woman's career at Budi Luhur University is the balance, the constant development of husband-wife relationships and the continuous development of relationships with children